A retrospective study investigating the anxiety and depression level of novel coronavirus Omicron patients in 2022. Issue 51 (23rd December 2022) - Pu, Yuting; Zhang, Wen; Xu, Xiangru; Sun, Yuting; Chen, Caiyu; Zhou, Shuang; Fang, Bangjiang
Abstract : Introduction: The novel coronavirus disease 2019 continues to spread widely, not only causing physical disorders in patients but also impairing mental health, bringing a heavy burden on global public health. This study aimed to evaluate the anxiety and depression status of patients infected with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) omicron variant in Shanghai. Methods/design: This study aimed to retrospectively analyze 2000 patients infected with the SARS-CoV-2 Omicron variant. Data from patients assessed with demographic information, anxiety and depressive symptoms were collected using a questionnaire. Clinical and laboratory data were collected using electronic medical system. Anxiety and depression were assessed using the Self-Rating Anxiety Scale, the Generalized Anxiety Disorder Scale, and the Patient Health Questionnaire. Clinical information and laboratory indicators included age, sex, blood pressure, blood glucose, basic disease, time of diagnosis onset, duration of hospitalization, vaccination status of novel coronavirus disease 2019, and virus-negative conversion time. Discussion: This study will provide evidence-based suggestions for early psychological intervention in patients infected with the SARS-CoV-2 Omicron Variant.